Analisis Kemampuan Self-Efficacy Siswa pada Pembelajaran Kooperatif Tipe Jigsaw - Purba, Tuty Novelindah; Sihombing, Susi; Silalahi, Lulu; Sinaga, Wita; Marpaung, Riko; Panjaitan, Simon; Hutauruk, Agusmanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to analyze the ability of self-efficacy using the jigsaw cooperative model, including (1) student self-efficacy after jigsaw cooperative learning and (2) the level of active student activity during the learning process. This research is a qualitative descriptive study. The subjects in this study were 34 students of X-IPA2 N 1 PAGARAN and the object of this research was the students' self-efficacy abilities and active student activities. The instrument used consisted of a self-efficacy questionnaire, student activity observation sheets, and interview guidelines. Data analysis used the Mile and Huberman model. The results showed that the self-efficacy of 34 students obtained high self-efficacy of 26.47%, moderate self-efficacy of 61.76% and low self-efficacy of 11.76%. Overall self-efficacy of students is 73.31 in the medium category. Conclusions, based on the data obtained, students' thinking processes on abilities; 1) The self-efficacy of SMA N 1 PAGARAN students after jigsaw type cooperative learning is good; 2) The overall percentage of active student activities used during teaching and learning activities is within the specified ideal time tolerance interval. Keywords: active student activity, ability, jigsaw cooperative type, self-efficacy